Effect of spacer groups on the performance of MCM-41-supported platinum cluster-derived hydrogenation catalysts - Maity, Niladri; Basu, Susmit; Mapa, Maitri; Rajamohanan, Pattuparambil R.; Ganapathy, Subramanian; Gopinath, Chinnakonda S.; Bhaduri, Sumit; Lahiri, Goutam Kumar (Journal of Catalysis, 2006)
MCM-41 was functionalized with (EtO)(3)SiCH2Cl, (MeO)(3)SiCH2CH2CH2Cl, and (CH3)Cl2SiCH2Cl. The functionalized materials were characterized by solid-state NMR (CPMAS, Si-29 and C-13) and XPS. The NMR data indicate that three new silicon environments were created by(EtO)(3)SiCH2Cl and (MeO)(3)SiCH2CH2CH2Cl, whereas with (CH3)Cl2SiCH2Cl, two new silicon environments were obtained. XPS results from Si 2p core level and the valence band from the material functionalized by (MeO)(3)Si(CH2)(3)Cl was found to be the same as that of the corresponding fresh catalyst (1a), in contrast to that of the materials functionalized by the other two silane reagents. After further functionalization with triethylamine, these materials were used as inorganic anion exchangers to support the cluster anion [Pt-12(CO)(24)](2-). Solid-state NMR (29Si, C-13, N-15) was used to establish the presence of the quaternary ammonium group in the cluster-supported species. Analogous materials were also created using fumed silica as the support, and all of the cluster-supported materials were tested as catalysts for the hydrogenation of methyl pyruvate, acetophenone, nitrobenzene, benzonitrile, ethylacetoacetate, 4-nitrotoluene, cyclohexanone, allyl alcohol, and styrene. The best activity was obtained for the catalyst that had MCM-41 as the support and chloropropyl as the spacer group. TEM showed that the supports and the spacer groups had observable effects on the platinum crystallite size of the catalysts. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: functionalized inorganic oxides; hydrogenation catalysts; MCM-41; platinum carbonyl cluster; Solid-state NMR; spacer groups; XPS